Temporal Stability of Self‐Reported Trauma Exposure on the Life Events Checklist for DSM‐5. Issue 1 (21st October 2020) - Pugach, Cameron P.; Nomamiukor, Faith O.; Gay, Natalie G.; Wisco, Blair E.
Abstract: The Life Events Checklist for DSM‐5 (LEC‐5) is a comprehensive screening instrument used to detect exposure to a range of potentially traumatic events. Despite its widespread use, research assessing the psychometric properties of scores on the LEC‐5—and trauma exposure more broadly—is scarce. Using a large sample of undergraduate students ( N = 1, 013), we sought to evaluate the reliability of trauma exposure reporting on the LEC‐5 across 8‐ ( N = 379) and 12‐week ( N = 343) intervals. Reliability estimates were examined for trauma exposure type (e.g., experiencing, witnessing), traumatic event type (e.g., sexual assault), and index trauma (i.e., "worst event") reporting. Reliability was more stable for events that were directly experienced, intraclass correlation coefficients (ICCs) = .62–64, than events that were witnessed, ICCs = .47–.52, or learned about, ICCs = .48–.53. Test–retest agreement was fair to good for reports of sexual assault, physical assault, transportation accidents, natural disasters, and other sexual experiences, κs = .49–.72, but only when individuals directly experienced these events. By contrast, across both assessment intervals, the agreement was attenuated, all κs < .40, for events that individuals witnessed or learned about regardless of event type. For index events, only sexual assault and sudden accidental or violent deaths were consistently reported with a fair or better agreement, κs = .42–.64. These findings suggest that reliable trauma reporting varies largely based on the nature of the traumatic event, yielding important implications for the assessment of DSM‐5 Criterion A and posttraumatic stress disorder. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐20‐0098.R2_Pugach_cantonese Traditional Chinese 使用DSM‐5的生活事件清單進行自我描述的創傷暴露的可靠性 摘要 : DSM‐5生活事件清單(LEC‐5 )是一個綜合的篩查工具, 用於檢測暴露於一系列潛在的創傷事件。儘管LEC‐5 被廣泛使用, 但評估LEC‐5分數的心理測量特性和更廣泛的創傷暴露的研究卻很少。我們使用一個大型的本科生樣本(N = 1, 013 ), 試圖評估LEC‐5的創傷暴露報告在8週(N = 379 )和12週(N = 343 )間隔內的可靠性。對創傷暴露類型(如經歷、目睹)、創傷事件類型(如性侵犯)和指標創傷(即「最壞事件」 )報告的可靠性估計進行了研究。直接經歷的事件的可靠性更穩定, 類內相關係數(ICCs )=0.62‐64, 而目睹的事件的可靠性則更穩定, ICCs = .47‐.52, 或了解到的情況, ICCs=. 48‐.53 。對於性攻擊、身體攻擊、交通事故、自然災害以及其他性經歷的報告, 重新測試的一致性是相當好的, κs =0.49‐0.72, 但只有當個人直接經歷了這些事件時, 才會有這種一致性。相比之下, 在兩個評估區間內, 對於個人目睹或了解的事件, 無論事件類型如何, 其一致性都有所減弱, 所有κs都<0.40 。對於指標事件, 只有性侵犯和突發意外或暴力死亡的報告具有一般或更好的一致性, κs =0.42‐0.64 。這些發現表明, 可靠的創傷報告主要根據創傷事件的性質而變化, 對DSM‐5標準A和創傷後壓力的評估具有重要意義。 Simplified Chinese 使用DSM‐5的生活事件清单进行自我描述的创伤暴露的可靠性 摘要 : DSM‐5生活事件清单(LEC‐5 )是一个综合的筛查工具, 用于检测暴露于一系列潜在的创伤事件。尽管LEC‐5 被广泛使用, 但评估LEC‐5分数的心理测量特性和更广泛的创伤暴露的研究却很少。我们使用一个大型的本科生样本(N = 1, 013 ), 试图评估LEC‐5的创伤暴露报告在8周(N = 379 )和12周(N = 343 )间隔内的可靠性。对创伤暴露类型(如经历、目睹)、创伤事件类型(如性侵犯)和指标创伤(即「最坏事件」 )报告的可靠性估计进行了研究。直接经历的事件的可靠性更稳定, 类内相关系数(ICCs )=0.62‐64, 而目睹的事件的可靠性则更稳定, ICCs = .47‐.52, 或了解到的情况, ICCs=. 48‐.53 。对于性攻击、身体攻击、交通事故、自然灾害以及其他性经历的报告, 重新测试的一致性是相当好的, κs =0.49‐0.72, 但只有当个人直接经历了这些事件时, 才会有这种一致性。相比之下, 在两个评估区间内, 对于个人目睹或了解的事件, 无论事件类型如何, 其一致性都有所减弱, 所有κs都<0.40 。对于指标事件, 只有性侵犯和突发意外或暴力死亡的报告具有一般或更好的一致性, κs =0.42‐0.64 。这些发现表明, 可靠的创伤报告主要根据创伤事件的性质而变化, 对DSM‐5标准A和创伤后压力的评估具有重要意义。